Host immune‐inflammatory markers to unravel the heterogeneous outcome and assessment of patients with PD‐L1 ≥50% metastatic non‐small cell lung cancer and poor performance status receiving first‐line immunotherapy. Issue 3 (22nd December 2021) - Banna, Giuseppe L.; Tiseo, Marcello; Cortinovis, Diego L.; Facchinetti, Francesco; Aerts, Joachim G. J. V.; Baldessari, Cinzia; Giusti, Raffaele; Bria, Emilio; Grossi, Francesco; Berardi, Rossana; Morabito, Alessandro; Catino, Annamaria; et al.
Abstract: Background: Patients with programmed cell death‐ligand 1 (PD‐L1) ≥50% metastatic non‐small cell lung cancer (mNSCLC) and ECOG performance status (PS) of 2 treated with first‐line immunotherapy have heterogeneous clinical assessment and outcomes. Methods: To explore the role of immune‐inflammatory surrogates by the validated lung immuno‐oncology prognostic score (LIPS) score, including the neutrophil‐to‐lymphocyte ratio (NLR) and the pretreatment use of steroids, alongside other prognostic variables. A retrospective analysis of 128 patients with PS2 and PD‐L1 ≥50% mNSCLC treated between April 2018 and September 2019 with first‐line pembrolizumab in a real‐world setting was performed. Results: With a median follow‐up of 15.3 months, the 1‐year overall survival (OS) and median progression‐free survival (PFS) were 32.3% (95% CI: 30.9–33.9) and 3.3 months (95% CI: 1.8–4.7), respectively. The NLR, lactate dehydrogenase (LDH) and pretreatment steroids results were the only significant prognostic factors on the univariate analysis and independent prognostic factors by the multivariate analysis on both OS and PFS. The LIPS score, including the NLR and pretreatment steroids, identified 29 (23%) favourable‐risk patients, with 0 factors, 1‐year OS of 67.6% and median PFS of 8.2 months; 57 (45%) intermediate‐risk patients, with 1 factor, 1‐year OS 32.1% and median PFS 2.7 months; 42 (33%) poor‐risk patients, with both factors, 1‐year OS of 10.7% and median PFS of 1.2 months. Conclusions: The assessment of pre‐existing imbalance of the host immune response by combined blood and clinical immune‐inflammatory markers may represent a way to unravel the heterogeneous outcome and assessment of patients with mNSCLC and poor PS in the immune‐oncology setting. Abstract : LIPS‐based suggestions for the first‐line treatment of patients with mNSCLC with PD‐L1 ≥ 50% and ECOG PS 2. The LIPS consists of the following validated prognostic factors: use of pretreatment steroids, NLR ≥4. The OS curve refers to all patients according to the LIPS score and corresponds to Figure 1A. For further details, see Figure 1 legend.